Public Health Promotion Efforts in Overcoming Diabetes in Patients of Class III Brawijaya Hospital Surabaya - Subarkat Bangun Satoto; Katmini; Yuly Peristiowati (Universitas STRADA Indonesia, 2025)
Brawijaya Hospital III Surabaya faces serious challenges due to the increasing prevalence of diabetes, requiring public health promotion efforts to address lifestyle factors, unhealthy eating habits, and lack of physical activity as the main triggers. The purpose of this community service is to promote public health in overcoming diabetes in patients of Brawijaya Hospital III Surabaya. The method used is fishbone by finding the cause and root of the problem.The results show that Brawijaya Hospital Class III Surabaya has identified the need to improve health promotion strategies through education, seminars, workshops, health campaigns, and collaboration with local governments, health institutions, and communities. The use of information technology, such as health applications, supports monitoring of diabetes patients and provides up-to-date information. The intervention plan includes education on healthy eating patterns, exercise, routine monitoring, counseling in the community, and development of digital applications for diabetes management. It is concluded that community health promotion efforts based on collaboration and technology can effectively overcome diabetes. It is recommended to strengthen cross-sector collaboration, utilize technology optimally, and implement ongoing education to encourage changes in people's lifestyles.